Rancang Bangun Sistem Informasi Penjualan Gas Pada CV. Berkat Alam Sejahtera - Salasa, Natsir; Arifin, Mochammad; Erstiawan, Martinus Sony (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
CV. Berkat Alam Sejahtera is a company engaged in the distribution of gas. CV. Berkat Alam Sejahtera supply gaseous oxygen, nitrogen, carbon dioxide, argon and acytelene. The company's customers in general hospitals, industries and companies engaged in the service. To date CV. Berkat Alam Sejahtera has more than 150 customers and gas sales target of at least 1700 tubes per month.Sales admin section is very difficult to determine the due date of each customer as well as reports of each customer receivable. In the process of registration of new customers, they often occur enrollment same customer and the customer long search process because of the large customer data. Parts sales admin difficulty in monitoring the stock tubes in the warehouse. Based on the results of a test application on the Market Surya it was concluded that the application can provide reminders the due date for the next week, so the delay in payment of debts can be reduced, the application can provide inventory information tubes are available in the warehouse, so the admin section of the sale is not the difficulty in monitoring the stock tube in the warehouse, for the registration of new customers, in order to avoid the occurrence of the same customer registration and the process of finding customers time because the number of data subscribers.Keywords: information systems, gas sales, sales, desktop.